URINARY TRACT INFECTION IN SPINAL CORD INJURIES - Rahimkhani, Monireh; Nikfalah, Abolghasem; Saberian, Mostafa; Mordadi, Alireza; Varmazyar, Sajad; Tavakoli, Ali (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Spinal cord injuries are typically associated with major trauma from motor vehicle accidents, falls, sports injuries, and violence. Urinary Tract Infections (UTI) is one of the most frequent conditions seen in spinal cord injuries patients. Diagnosis is not always easy due to lack of symptoms. Present study is survey about urinary tract infection and pyuria in these patients. Methods: All of patients with spinal cord injuries, who admitted to Brain and Spinal Injury Repair Research Centreâ€ in Imam Hospital in duration one year, were included in this study. Clean catch midstream urine samples were collected of patients and were analyzed by biochemical and microscopically surveys. Results: In total 103 patients, 22 patients have cervical spinal cord injury, 52 patients have thoracic spinal cord injury and 13 patients have lumbar spinal cord injury. 83 patients were urine culture positive with urinary tract infection and pyuria were seen in 65 patients. the highest incidence of UTI and pyuria were demonstrated in patients with cervical spinal cord damage. E.coli, Klebsiellapneumoniea and Enterobacter cloacae were isolated in urine samples respectively. the high incidence of resistancy to Nitrofurantoin and Imipenem in E.coli were seen. Conclusion: Patients with spinal cord injuries have to use catheter for long time and or for all of life, and they are high risk to recurrent urinary tract infections and other infections. These patients need to monitor for urinary tract infection although without any symptoms of infections and sometimes they need to take prophylactic antibiotics. Â Key words: spinal cord injury, urinary tract infection, pyuria.Â